Sistem Informasi Pembayaran Wi-Fi Menggunakan QR Code di CV Bagus Agung Mandiri Sejahtera - Anne Rufaedah; Mochaamad David Hariono; Trimurti Wisnu Prayogo; Muhamad Yusuf Anap Hani; Achmad Abdan Sakur; Indyah Hartami Santi (LPPM STIMATA, 2024)
CV Bagus Agung Mandiri Sejatera (CV BAMS), one of the CV (Commanditaire Vennotschaap) Wi-Fi service providers in the Blitar area, currently serves 3 regions and serves 800 customers. In the Wi-Fi monthly bill payment process, there are problems in the process of finding customer IDs and the number of payment recap documents that are input manually. Therefore, a Wi-Fi payment information system using a QR Code is needed. This system aims to manage payment data by scanning QR Code on customer cards and using them as data sources to generate reports and recaps to owners in the form of PDF files. This Wi-Fi Payment Information System with QR Code was built using the Waterfall Method. The stages carried out are requirements, design, implementation, testing and maintenance. Testing this system uses a questionnaire method which was done with the user, and as a result, this Wi-Fi payment information system brings positive benefits to business development and solves existing problems.